Upaya Meningkatkan Moral Anak Usia Dini Melalui Metode Bercerita Dengan Media Wayang Kreasi Kelompok A Di TK Rimapersada - Jubaedah, Endah; Hazizah, Siti Windy (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2024)
Based on first observations, several problems were found in early childhood, namely the low moral values ​​of early childhood due to the inappropriate moral application of children. One of the factors that hinders moral development is that children often see behavior that is not in accordance with moral values ​​in their surroundings. So it is necessary to take action, namely increasing morale through the storytelling method with creative wayang media. The storytelling method is one of the most widely used methods for increasing children's morale, usually there is a moral message contained in the story. Apart from that, storytelling can also use media, one of which is creative wayang media. Puppet creations are used so that children are interested in listening to stories and can make children more enthusiastic about participating in activities. The purpose of this study is to improve the morale of early childhood at Rimapersada Kindergarten using the storytelling method with creative puppets. The type of research conducted was classroom action research (PTK) designed by Kemmis and Tagart, using qualitative methods. Observations, interviews and documentation were carried out for data collection. The research subject was the moral development of children with 15 children consisting of 8 girls and 7 boys as objects. The results of the study showed an increase in children's morale from the results of initial observations, namely 26% in the category of children who developed according to expectations and developed very well, to 46% in cycle I. In cycle II, it increased according to expectations to 87%. This shows the significance of increasing the morale of early childhood through the storytelling method using creative wayang media. Kata kunci: early childhood morality, storytelling method, creative wayang media